In nomine Zappa, Zappatore: Sketch of an Hypothesis (S/Z2) + (sv/gw) - Rea, John (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2004)
A man's character is, as Heraclitus once observed, his destiny. Similarly, Frank Zappa noted that "You are what you is". In nomine Zappa, Zappatore proposes a philological as well as iconographic deconstruction of the Italian name/mask (persona), Zappa. The essay suggests that not only is a man's character his daimon but that, moreover, FZ was both an assiduous and subversive artistic worker.